The portrayal of Europe and America in Nigerian newspapers: the other edge of dependency (2009)
"Dependency is a term that refers to one of the strands of the imbalances in international news flow between the West and less developed countries (LDC). Western news agencies, it has been observed, have cornered the whole process of global newsgathering so totally that LDC media depend on them to get almost any news about the West and other LDC. Since these agencies carry mostly negative news about LDC, dependency, it has been alleged, promotes the dissemination of negative news about LDC both in the West and among LDC. This paper, however, takes on a side of the argument that seems to have escaped notice—the negative impact of dependency on the image of the West. The paper content-analysed the foreign news pages of 262 editions of two leading newspapers in Nigeria and found that most (66%) of the news stories these papers disseminated about the West were negative, and all these were received from Western news agencies. Most of the news stories focused on wars, terrorism and politics. They are such that paint the West as unsafe. The paper concludes that though dependency is pemicious to the image of the LDC, it is by no means favourable to the image of the West. It is double-edged. "